Pengaruh Olahraga Permainan Tradisional Congklak Terhadap Perkembangan Psikomotorik dan Kognitif Siswa Sekolah Dasar - Apriyanda Apriyanda; Nur Kibah Mandasari Lubis; Niko Alriadi Sinaga; Anthony Chornelius Nadeak; Fajar Siddik (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Traditional sports and games, such as congklak, have been an inseparable part of culture and people's lives since ancient times. This research aims to reveal the influence of the congklak game on psychomotor and cognitive development in elementary school students. By comparing groups of students who regularly play congklak and those who don't, this research wants to find out whether this traditional game can improve students' fine motor skills, hand-eye coordination, counting ability, and problem-solving ability. It is hoped that the results of this research can contribute to cultural preservation and improving the quality of education by integrating traditional games as an effective learning medium.